RANCANG BANGUN SISTEM INFORMASI PENDAFTARAN PASIEN KLINIK PRATAMA ALMIRA BOGOR - Muhammad Yasin; Audi Nestaldi (POLITEKNIK LP3I JAKARTA, 2023)
The problem at Almira Primary Clinic is that patient registration is still done manually, causing various obstacles in the management and storage of patient data. This manual process has the potential to cause errors in recording, duplication of data, delays in service, and difficulties in searching for patient data when it is needed again. In addition, storing data in physical archives also carries the risk of document loss and damage, which can hamper the performance of health services at the clinic. Based on these problems, this study aims to design and develop a web-based patient registration application that can help Almira Primary Clinic manage patient data more effectively, quickly, and accurately. The developed system is expected to simplify the patient registration process, speed up service flow, and improve the work efficiency of clinic administrative staff. This application is designed to be web-based so that it can be accessed easily and flexibly according to the operational needs of the clinic. In developing the system, the programming method used is the CodeIgniter 4 framework with MySQL database support as the data storage medium.